Investigation on the Mental Health Status of ICU Practitioners and Analysis of Influencing Factors During the Stable Stage of COVID-19 Epidemic in China - Wei He; Wenjin Chen; Xiaopeng Li; Sui Sum Kung; Liangnan Zeng; Tangming Peng; Xiaomeng Wang; Reng Ren; Di Zhao (Frontiers in Public Health, 2021)
Objective: To understand the impact of COVID-19 epidemic on the mental health status of intensive care unit (ICU) practitioners in China, and to explore the relevant factors that may affect the mental health status of front-line medical workers so as to adopt efficient and comprehensive measures in a timely manner to protect the mental health of medical staff.Methods: The study covered most of the provinces in China, and a questionnaire survey was conducted based on the WeChat platform and the Wenjuanxing online survey tool. With the method of anonymous investigation, we chose ICU practitioners to participate in the investigation from April 5, 2020 to April 7, 2020. The respondents were divided into two groups according to strict criteria of inclusion and exclusion, those who participated in the rescue work of COVID-19 (COVID-19 group) and those who did not (non-COVID-19 group). The SCL-90 self-evaluation scale was used for the evaluation of mental health status of the subjects.Results: A total of 3,851 respondents completed the questionnaire. First, the overall mental health status of the targeted population, compared with the Chinese norm (n = 1,388), was reflected in nine related factor groups of the SCL-90 scale, and significant differences were found in every factor in both men and women, except for the interpersonal sensitivity in men. Second, the overall mental health of the non-COVID-19 group was worse than that of the COVID-19 group by the SCL-90 scale (OR = 1.98, 95% CI, 1.682–2.331). Third, we have revealed several influencing factors for their mental health in the COVID-19 group, current working status (P < 0.001), satisfaction of diet and accommodation (P < 0.05), occupational exposure (P = 0.005), views on the risk of infection (P = 0.034), and support of training (P = 0.01).Conclusion: The mental health status of the ICU practitioners in the COVID-19 group is better than that of the non-COVID-19 group, which could be attributed to a strengthened mentality and awareness of risks related to occupational exposure and enforced education on preventive measures for infectious diseases, before being on duty.